Économie multinationale et contrôle gouvernemental : Le cas de la Belgique - Quévit, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1985)
The article maintains that, with its long tradition of an open economy the State could not play the role of guiding the economic development of the country. The investment of foreign MNE in the Belgian economy has had major destabilizing effects in the regional structure: foreign direct investment was almost entirely done in Flanders. Simultaneously, the Belgian MNE disinvest in order to flee to the fiscal heaven of the neighbour Luxembourg. If the nation-state has played any role toward both foreign and local MNE, it has promoted multinationalization.